2015
DOI: 10.1155/2015/682476
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation Behavior and System Properties of Aqueous Two-Phase Systems with Polyethylene Glycol and Different Salts: Experiment and Correlation

Abstract: The phase separation behaviors of PEG1000/sodium citrate, PEG4000/sodium citrate, PEG1000/ammonium sulfate, and PEG4000/ammonium sulfate aqueous two-phase systems were investigated, respectively. There are two distinct situations for the phase separation rate in the investigated aqueous two-phase systems: one state is top-continuous phase with slow phase separation rate and strong bottom-continuous phase with fast phase separation rate and weak volume ratio dependence. The system properties such as density, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Phase separation might require time because the molecules need to achieve a threshold extent of intermolecular interactions to assemble for the formation of droplets . Several studies have indeed reported LLPS after a certain period of incubation time for a diverse set of proteins, including α-Syn. ,, Notably, near the binodal LLPS boundary, the protein concentration may be just above the critical concentration but not high enough to induce LLPS immediately . In this region, the droplet assembly is delayed and the droplets formed in this region need to reach a threshold size to stabilize and grow further .…”
Section: Discussionmentioning
confidence: 99%
“…Phase separation might require time because the molecules need to achieve a threshold extent of intermolecular interactions to assemble for the formation of droplets . Several studies have indeed reported LLPS after a certain period of incubation time for a diverse set of proteins, including α-Syn. ,, Notably, near the binodal LLPS boundary, the protein concentration may be just above the critical concentration but not high enough to induce LLPS immediately . In this region, the droplet assembly is delayed and the droplets formed in this region need to reach a threshold size to stabilize and grow further .…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the obtained data in Fig. 3 with the results of Yuan and co-workers 45 , Mobalegholeslam and Bakhshi 46 in the aqueous two phase system (ammonium sulfate and PEG) without cobalt ions and with protein reported by Dumetz and co-workers 47 is shown in Fig. 4 .…”
Section: Resultsmentioning
confidence: 67%
“…Adding to this, citrate is a biodegradable and non-toxic anion, making this molecule more environmentally friendly than other salts used for ATPS. 14,42 As can be seen in Fig. 3 and Table 2, the partition of proteins in PEG 6000-citrate ATPS was slightly different between CMN and CAT venoms.…”
Section: Partition Of Clarified Venomsmentioning
confidence: 80%
“…Therefore, is more likely that proteins migrate towards the citrate‐rich phase in comparison to the phosphate‐rich phase. Adding to this, citrate is a biodegradable and non‐toxic anion, making this molecule more environmentally friendly than other salts used for ATPS 14,42 …”
Section: Resultsmentioning
confidence: 99%